Dıstalızatıon Of Upper Fırst Molar Wıth Open-Coıl Jıg Applıance - Turgut Kansız; Hüseyin Ölmez; Yalçın Işımer (Galenos Yayinevi, 1996)
The purpose of the study is, to use the extra-oral forces and the open-coil jig appliance in the distalization of the upper first molars on the individuals to compare the success, advantages and disadvantages of the methods and to discuss their importance in orthodontic treatment. A total of 20 individuals are representing the research group. Upper right and left 20 molars of 10 individuals are distalized with the use of extraoral fores and another group of upper right, and left 20 molars are distalized with open-coil jig appliance. 40 lateral cephalometric roentgenographs are taken to search the degree of distalization, the skeletal and dental axial angular variations before and after the orthodontic treatment. Average of age in the molar distalization group with extraoral forces is 11.2 years and in the open-coil jig appliance group is 11.4 years. Upper first molars are distalized with valuable importance in both groups. In the open-coil jig group, the upper first molars are distalized faster and more when compared with the headgear group within average of 2 months. The axial inclinations of second premolars and central incisors are increaed in open-coil jig group when compared with heagdear group.